Policy-making on science in society between Europeanization and core–periphery divide. Issue 1 (2nd January 2016) - Lažnjak, Jasminka; Švarc, Jadranka
Abstract : The aim of the paper is to identify the cross-national differences and similarities in policy-making trends on science in society (SiS) based on the comparative analysis of national reports from FP7 project "Monitoring Policy and Research Activities Related to Science in Society in Europe". Science in society in EU is characterized by two parallel processes: Europeanization and diversity of science and innovation policies. The focus of the analysis is to explore the possible indications of Europeanization as well as diversities and find elements of certain elements of core–periphery model. The focus of the analysis is to explore the existence of common issues of SiS and on the other side different policy actions and national priorities. Although the analysis reveals the presence of Europeanization process diversities and divides are still present which draws attention to a core–periphery model. While common trends can be recognized on the theoretical and contextual level mainly coming from the various processes of Europeanization, the core–periphery model is simultaneously present on the practical level of governance and policy-making.